A Novel Multi‐hidden Semi‐Markov Model for Degradation State Identification and Remaining Useful Life Estimation. (8th October 2012) - Su, Chun; Shen, Jinyun
Abstract With the increase of product reliability, collecting time‐to‐failure data is becoming difficult, and degradation‐based method has gained popularity. In this paper, a novel multi‐hidden semi‐Markov model is proposed to identify degradation and estimate remaining useful life of a system. Multiple fused features are used to describe the degradation process so as to improve the effectiveness and accuracy. The similarities of the features are depicted by a new variable combined with forward and backward variables to reduce computational effort. The degradation state is identified using modified Viterbi algorithm, in which linear function is adopted to describe the contribution of each feature to the state recognition. Subsequently, the remaining useful life can be forecasted by backward recursive equations. A case study is presented, and the results demonstrate the validity and effectiveness of the proposed method. Copyright © 2012 John Wiley & Sons, Ltd.